2020
DOI: 10.21203/rs.3.rs-111875/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Handgrip strength and its association with noncommunicable diseases and their risk factors among elderly individuals in Malaysia

Abstract: Background: Handgrip strength (HGS) is indicative of overall physical health among older people. A reduction in HGS may be associated with an increased risk of disease. This study aims to assess the association between HGS and noncommunicable diseases (NCDs) and the related risk factors.Methods: One thousand two hundred four (1204) participants from four areas in Selangor state, Malaysia, were recruited. A comprehensive face-to-face interview based on the Bahasa Malaysia version of the Japan Gerontological Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In Malaysia, other researchers conducted a study among the elderly to assess the association between HGS and noncommunicable diseases (NCDs) and the related risk factors [16]. This study revealed that the amount of HGS levels fell dramatically as a person grew older and was higher in males.…”
Section: A Study On the Correlation Between Hand Grip And Age Using S...mentioning
confidence: 99%
“…In Malaysia, other researchers conducted a study among the elderly to assess the association between HGS and noncommunicable diseases (NCDs) and the related risk factors [16]. This study revealed that the amount of HGS levels fell dramatically as a person grew older and was higher in males.…”
Section: A Study On the Correlation Between Hand Grip And Age Using S...mentioning
confidence: 99%